Sld3-MCM Interaction Facilitated by Dbf4-Dependent Kinase Defines an Essential Step in Eukaryotic DNA Replication Initiation - Fang, Dingqiang; Cao, Qinhong; Lou, Huiqiang (Frontiers in Microbiology, 2016)
Sld3/Treslin is an evolutionarily conserved protein essential for activation of DNA helicase Mcm2-7 and replication initiation in all eukaryotes. Nevertheless, it remains elusive how Sld3 is recruited to origins. Here, we have identified the direct physical association of Sld3 with Mcm2 and Mcm6 subunits in vitro, which is significantly enhanced by DDK in vivo. The Sld3-binding domain (SBD) is mapped to the N termini of Mcm2 and Mcm6, both of them are essential for cell viability and enriched with the DDK phosphorylation sites. Glutamic acid substitution of four conserved positively charged residues of Sld3 (sld3-4E), near the Cdc45-binding region, interrupts its interaction with Mcm2/6 and causes cell death. By using a temperature-inducible degron (td), we show that deletion of Mcm6 SBD (mcm6ΔN122) abolishes not only Sld3 enrichment at early origins in G1 phase, but also subsequent recruitment of GINS and RPA during S phase. These findings elucidate the in vivo molecular details of the DDK-dependent Sld3-MCM association, which plays a crucial role in MCM helicase activation and origin unwinding.